Areally Extensive Surface Bedrock Exposures on Mars: Many Are Clastic Rocks, Not Lavas. Issue 4 (28th February 2018) - Rogers, A. Deanne; Warner, Nicholas H.; Golombek, Matthew P.; Head, James W.; Cowart, Justin C.
Abstract: Areally extensive exposures of intact olivine/pyroxene‐enriched rock, as well as feldspar‐enriched rock, are found in isolated locations throughout the Martian highlands. The petrogenetic origin(s) of these rock units are not well understood, but some previous studies favored an effusive volcanic origin partly on the basis of distinctive composition and relatively high thermal inertia. Here we show that the regolith development, crater retention, and morphological characteristics for many of these "bedrock plains" are not consistent with competent lavas and reinterpret the high thermal inertia orbital signatures to represent friable materials that are more easily kept free of comminution products through eolian activity. Candidate origins include pyroclastic rocks, impact‐generated materials, or detrital sedimentary rocks. Olivine/pyroxene enrichments in bedrock plains relative to surrounding materials could have potentially formed through deflation and preferential removal of plagioclase. Plain Language Summary: The Martian surface is dominated by loose dust, sands, and rocks, but high spatial resolution imaging has permitted the detection of numerous flat‐lying exposures of ancient, intact bedrock. These "bedrock plains" have previously been interpreted as lava sequences, perhaps similar to lava plains found in the dark parts of the lunar nearside. Here we show evidence that bedrock plains may instead be composed of sedimentary rocks, airfall volcanic ash, or impact‐generated airfall materials. First, the bedrock plains should have developed a thick regolith over time, due to repeated pummeling by impactors over billions of years. But they lack a regolith, suggesting that they break up easily into fine particles that are then easily moved away from the bedrock by wind. Second, the bedrock plains show morphologies that are similar to wind‐eroded soft rocks on Earth. Third, the bedrock plains have fewer small craters than adjacent surfaces, likely due to the relative ease in which craters can be erased through erosion. Bedrock plains are found at all of the proposed landing sites for the upcoming Mars2020 rover; nonlava origins of these rocks should be considered. Direct analysis of these rocks will provide insight into the origin(s) of these globally important materials. Key Points: Many bedrock plains are likely composed of mechanically weak rocks Potential origins include lithified detrital sediments, pyroclastics, or impact‐generated materials High thermal inertia may indicate relatively friable rocks, due to ease of comminution product removal and exposure of lithified surface